Pembentukan Karakter Remaja Melalui Pendidikan Kepramukaan pada Gugus Depan Sunan Ampel - Humaidy, Muhamad; Darlan, Saifullah; Suparman, Suparman (Pedagogik: Jurnal Pendidikan, 2024)
This research aims to determine the contribution of scouting activities in shaping the character of students as members of the Scout Group at Sunan Ampel MTsN 2 Palangka Raya. A qualitative approach was employed to provide pertinent information in line with the research objectives. Data collection methods included observation, interviews, and documentation. The research subjects and informants consisted of mentors, trainers, and students participating in the Scout Group at Sunan Ampel MTsN 2 Palangka Raya. Data analysis was conducted concurrently, encompassing data collection, condensation, display, verification, and drawing conclusions. The findings suggest that character formation of students through scouting activities in the Scout Group at Sunan Ampel MTsN 2 Palangka Raya is highly effective and significantly contributes to their character development. This is achieved through the integration of character values into scouting activity training materials, such as marching exercises, camping, and hiking. This integration fosters students' consciousness of God Almighty, upholds Pancasila principles, promotes discipline, independence, and enhances sensitivity to social issues.